2021
DOI: 10.3389/fpsyg.2021.644096
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Academic Effects of Studying From the Home and Host Country During the COVID-19 Pandemic

Abstract: Objective: This study explored the psychological and academic effects of studying online from the home vis-à-vis host country during the coronavirus disease 2019 (COVID-19) pandemic in the experience of international students at the University of Warsaw, Poland.Methods: A total of 357 international students from 62 countries (236 in the host country and 121 in the home country) completed an online questionnaire survey 2 months after transition to online learning. We studied students' levels of loneliness, life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 43 publications
5
48
1
5
Order By: Relevance
“…In a questionnaire probing the mental health of medical college students, Cao et al (2020) found that risk factors increasing anxiety were economic consequences as well as having relatives or acquaintances infected with SARS-CoV-2, while social support, living with parents, and family income stability were protective factors. Similar results were obtained by Wilczewski et al (2021), whose investigation of the psychological and academic effects of learning online among international students enrolled at the University of Warsaw revealed that those who had returned to their home countries (and therefore likely had familial support) exhibited higher academic adjustment, while quarantine and self-isolation increased the levels of lonelinessand acculturative stress when in the host country. Amendola et al (2021) study carried out among students in Switzerland showed that anxiety symptoms decreased with time, and its levels were predicted by older age, female gender, out-of-country nationality, loneliness, concerns about own health (positively), and resilience and social support (negatively).…”
Section: Literature Reviewsupporting
confidence: 76%
“…In a questionnaire probing the mental health of medical college students, Cao et al (2020) found that risk factors increasing anxiety were economic consequences as well as having relatives or acquaintances infected with SARS-CoV-2, while social support, living with parents, and family income stability were protective factors. Similar results were obtained by Wilczewski et al (2021), whose investigation of the psychological and academic effects of learning online among international students enrolled at the University of Warsaw revealed that those who had returned to their home countries (and therefore likely had familial support) exhibited higher academic adjustment, while quarantine and self-isolation increased the levels of lonelinessand acculturative stress when in the host country. Amendola et al (2021) study carried out among students in Switzerland showed that anxiety symptoms decreased with time, and its levels were predicted by older age, female gender, out-of-country nationality, loneliness, concerns about own health (positively), and resilience and social support (negatively).…”
Section: Literature Reviewsupporting
confidence: 76%
“…The cutoff points for a case finding are 10 for depression, 8 for anxiety, and 15 for stress. The depression subscale consists of items 3, 5, 10, 13, 16, 17, and 21 with scores ranging from normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), to extremely severe (28+). The anxiety subscale consists of items 2, 4, 7, 9, 15, 19, and 20, with scores ranging from normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), to extremely severe (20+).…”
Section: Depression Anxiety and Stress Scalesmentioning
confidence: 99%
“…The depression subscale consists of items 3, 5, 10, 13, 16, 17, and 21 with scores ranging from normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), to extremely severe (28+). The anxiety subscale consists of items 2, 4, 7, 9, 15, 19, and 20, with scores ranging from normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), to extremely severe (20+). Finally, the stress subscale consists of items 1, 6, 8, 11, 12, 14, and 18, with scores ranging from normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)…”
Section: Depression Anxiety and Stress Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2020) assessed the impact of the outbreak on stress, poor mental health, and poor sleep quality symptoms among college students in Guangdong. Wilczewski et al (2021) investigated the psychological and academic effects of learning online among international students enrolled at the University of Warsaw. Alemany-Arrebola et al (2020) analyzed the impact of trait-and state-anxiety on university students' perception of academic selfefficacy in Spain.…”
Section: Introduction: Background Literaturementioning
confidence: 99%